1983
DOI: 10.1111/j.1423-0410.1983.tb03660.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Blood Group Antigens from Storage at Low Ionic Strength in the Presence of Neomycin1

Abstract: Red blood cells (RBC) stored without plasma in a neomycin, low ionic strength medium at 4 degrees C in excess of 24 h show alterations in antigen reactivity. There is a loss of protease-sensitive RBC antigens and a protease-type increased IgG saline agglutinability of Rh antigens that is associated with increased binding of 125I anti-D. Both the serological findings and the alteration in RBC membrane polypeptides are consistent with protease modification of the membrane due to contamination of the RBC by leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…These events can be ascribed to endogenous red cell proteinases since the hypothetical effect of leukocyte lyso somal enzymes for ghost proteolysis [1,2,18,19,21] could be excluded by experiments in which leukocytes were re moved or where the addition of preservative solution did not result in WBC degranulation. Therefore, we hypothe size that damage to membrane structure during storage [22] may induce a subsequent susceptibility of ghost proteins to the action of endogenous proteinases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These events can be ascribed to endogenous red cell proteinases since the hypothetical effect of leukocyte lyso somal enzymes for ghost proteolysis [1,2,18,19,21] could be excluded by experiments in which leukocytes were re moved or where the addition of preservative solution did not result in WBC degranulation. Therefore, we hypothe size that damage to membrane structure during storage [22] may induce a subsequent susceptibility of ghost proteins to the action of endogenous proteinases.…”
Section: Discussionmentioning
confidence: 99%
“…red cells in plasma plus CPDA-1) most ghost proteolysis is delayed to the middle period of red cell storage. Although plasma antiproteinases are likely to play a role in inhibiting proteolytic activity on red cell mem branes [2], the simultaneous presence of additive solution…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malyska et al 67 showed that if RBCs were stored without plasma in a low ionic-strength medium containing neomycin, there was a loss of protease-sensitive antigens. Interestingly, there was an increased binding of anti-D and enhanced reactions with agglutinating anti-D.…”
Section: Lissmentioning
confidence: 99%